Challenger at sea : a ship that revolutionized earth science - Hsü, Kenneth J. (Kenneth Jinghwa), 1929- (Princeton legacy library, 1992)
The famous geological research ship Glomar Challenger was a radically new instrument that revolutionized earth science in the same sense that the cyclotron revolutionized nuclear physics, and its deep-sea drilling voyages, conducted from 1968 through 1983, were some of the great scientific adventures of our time. Beginning with the vessel's first cruises, which lent support to the idea of continental drift, the Challenger played a key part in the widely publicized plate-tectonics revolution and its challenge to more conventional theories. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.